Optimalisasi Digital Marketing Sebagai Media Informasi dan Pemasaran Produk Bagi Anggota Komunitas UMKM Naik Kelas - Widi Astuti; Lia Mazia; Johan Hendri Prasetyo; Fajar Sarasati; Jeri Dabi; Safira Maharani; Nabil Hanif Leksmono; Danang Rusdawindra Samiaji; Dennis Fathurahman (Jurnal Abdimas Perbanas, 2023)
MSME Community Class Up is an organizational forum which established with sense of togetherness as a result of the Covid-19 Pandemic, where MSME players really affected by significant decline in their business, within the Class Up of UMKM Community, those MSMEs are given training and workshops which can help them in turnover the decline in sales and choosing the right market strategies after the Covid-19 pandemic. By Optimizing the Digital Marketing as one of Information and Product Marketing Media for MSME Members of the MSME Community class up which seems very beneficial for MSMEs because by the use of digital marketing, MSMEs can make decisions about the sustainability of their business by applying digital-based marketing strategies for the businesses that they run. Good response from partners towards training are very useful in increasing partners' skills in introducing digital marketing and the participants were very enthusiastic and active in participating in the training by asking questions related to business strategy, as well as the implementation of digital marketing in business. The results of this training indicated that the participants had increase their ability in the use of various types of digital marketing media and their sales was increased by 80%. Through the capabilities which possessed by the partners in managing the optimization of digital marketing, so that they can assess their owned marketing performance periodically.